1996
DOI: 10.1007/978-3-7091-2678-3_71
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Critical Points in Robot Operations with an Artificial Vision System

Abstract: Stereo Vision for assisted robot operations implies the use of special purpose techniques to increase precision. A simple algorithm in the reconstruction of 3D trajectories by real-time tracking is described here, which has been extensively tested with promising results. If the form of the trajectory is known a priori, the interpolation of multiple real-time acquisition yields an increase of precision of about 25% of the initial error, depending on the uncertainty in locating the points within the image. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In any given application, the main tasks of a vision system (both in two and three dimensions) can be summarized as recognition [4] (including OCR), inspection (also measurement/gauging [3,5]) and localization (tracking if in motion [6]). Assembly can be considered a combination of all three: for instance an artificial vision system inspects mating [4,5] by identifying and by checking the relative position (and inclination) of the parts involved.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In any given application, the main tasks of a vision system (both in two and three dimensions) can be summarized as recognition [4] (including OCR), inspection (also measurement/gauging [3,5]) and localization (tracking if in motion [6]). Assembly can be considered a combination of all three: for instance an artificial vision system inspects mating [4,5] by identifying and by checking the relative position (and inclination) of the parts involved.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…This transformation is represented by 12 coefficients and requires a minimum of 6 non aligned points [6]. So although we have 16 control points in a row (= tip Centers of Gravity), we need at least 2 rows (or more, and solve the system in the least squares sense).…”
Section: Localization Strategymentioning
confidence: 99%
“…The machine vision inspection of stone is a topic that has received relatively little attention and although the number of publications in this area has been somewhat limited, a number of interesting studies have been reported, for example, by Lebrun at the University of Liege [8], Lanzetta at the University of Pisa [9], Smith at UWE [10][11][12] and others [13][14][15][16][17][18]. In addition, existing industrial devices for inspecting and measuring stone surface finish are marketed, and relevant patents are held, by DMO in Belgium [19].…”
Section: Machining Of Natural Stone Materialsmentioning
confidence: 99%